Annual Report 2020 of the Institute for Thermal Energy Technology and Safety - Tromm, Walter (KIT Scientific Reports, 2022)
The annual report of the Institute for Thermal Energy Technology and Safety of KIT summarizes its research activities and provides some highlights of each working group, like thermal-hydraulic analyses for fusion reactors, accident analyses for light water reactors, and research on innovative energy technologies: liquid metal technologies for energy conversion, hydrogen technologies and geothermal power plants. The institute has been engaged in education and training in energy technologies.